Collection of International Topics in Health Science- V1 2023
DOI: 10.56238/colleinternhealthscienv1-106
|View full text |Cite
|
Sign up to set email alerts
|

The Food Industry And The Manipulation Of The Masses Through Advertising

Abstract: The food industry emerged in the 17th century, after the Industrial Revolution, and gained strength with globalization and the rise of capitalism in the 1990s. This was due to the new shape of society, which went from being primarily agrarian and pastoral, with a lifestyle that followed the patterns of nature, to almost completely urban, with a modified and much more accelerated notion of time. The growing charge for productivity, at first in factory jobs, and now in large companies, has caused adaptations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(5 reference statements)
0
0
0
Order By: Relevance
“…Studies have indicated that customers' openness to trying plant-based foods is affected by factors including sustainable sourcing and personal advantages (Rombach & Dean, 2023). Food environments, which encompass food production, processing, and consumption, are influenced by cultural and taxonomic variety, as demonstrated in case studies conducted in the Lower Volga and the Republic of Peru (dos Santos et al, 2023). The concept of "food landscape" is employed in several ways, such as spatial analysis, social and cultural perspectives, behavioral studies, and systemic thinking.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that customers' openness to trying plant-based foods is affected by factors including sustainable sourcing and personal advantages (Rombach & Dean, 2023). Food environments, which encompass food production, processing, and consumption, are influenced by cultural and taxonomic variety, as demonstrated in case studies conducted in the Lower Volga and the Republic of Peru (dos Santos et al, 2023). The concept of "food landscape" is employed in several ways, such as spatial analysis, social and cultural perspectives, behavioral studies, and systemic thinking.…”
Section: Introductionmentioning
confidence: 99%